HUBUNGAN KADAR SENG SERUM DENGAN TINGGI BADAN ANAK SEKOLAH DASAR PENDERITA GAKY - Setijowati, Nanik (Jurnal Kedokteran Brawijaya, 2005)
The incidence goiter starts to the extend in Urban area. Not all Elementary School children with goiterexperience of pursued growth. This indicates that besides low iodine content, there are other elements which also influence growth. This research intends to study the relationship between zinc the level of serum and height on elementary school children (8 – 12 year) in endemic goitre areas, in Malang Municipality. Data ware collected with cross-sectional study from August to December 2000. Blood and urine sample of twenty  children of each group were examined for zinc serumand iodine urine concentration. Information about diet pattern, socio-economical condition were obtained by structured questionairre for mother and children.This research used Independent T-test, Person Correlation test, and Multiple Regression for statistics analysis. The result showed that: (1). There were significant relationships between energy (r= 0.364, p = 0.012); protein (r = 0.481, p = 0.001) and zinc intake (r =0.491, p = 0.001) with height; (2). There were significant difference in energy (p = 0.014), carbohydrate (p = 0.042), lipid( p = 0.014), protein (p = 0.003), and zinc intake(p = 0.004) between the two groups examined. The conclusion was that lower height for age was possibly ascribed to lack of energy, protein, iodine and zinc intake. Key words:zinc serum, iodine urine, height for age, and goiter